Strategi Komunikasi Pariwisata Dalam Meningkatkan Pendapatan Masyarakat Desa Lauwon - Wahyudi; Kisman Karinda; Falimu, Falimu (Yayasan Literasi Sains Indonesia, 2022)
Tourism is a potential to increase development that develops the noble values ​​that exist and are still being discovered today and preserved for the future. Communication is basically a social process carried out by individuals by using symbols to create and interpret similarities in meaning. The research objective is how tourism communication strategies increase the income of the Lauwon village community, East Luwuk District. The analytical approach of this research is carried out systematically by taking and compiling data obtained through interviews, observations and literature studies, classifying data, describing it into units, synthesizing, compiling into patterns, and choosing which ones to use. What is important, what will be researched, and draw conclusions that are easy to understand. The results of the research carried out that the communication strategy carried out through advertising and marketing and public relations although it has not increased too much but tourist sites are starting to get attention from the government and the Lauwon village community in the implementation of their management.